Enhancement of natural killer cell cytotoxicity by using static magnetic field to increase their viability. (3rd April 2019) - Lin, Shu-Li; Su, Yi-Tsai; Feng, Sheng-Wei; Chang, Wei-Jen; Fan, Kan-Hsin; Huang, Haw-Ming
ABSTRACT: Natural killer (NK) cells are innately immune to the body's immune system and can actively recognize and kill cancer cells. This study explores the potential for enhancing the killing ability of NK cells by co-culturing the NK cells with the target cells under a static magnetic field (SMF). In this study, NK92-MI cell lines were cultured in the presence of a 0.4-T SMF. The effect of the SMF on NK cell viability was evaluated by means of an MTT assay. Culturing tests were performed with inhibitors of the DAG/IP3, STAT3, ERK, JNK and p38 pathways in order to examine the possible signaling cascade responsible for the SMF effect on the NK92-MI cell viability. Finally, the effect of the SMF on the cytotoxicity of the NK92-MI cells was evaluated by co-culturing the NK cells with K562 leukemia cell lines. The results showed that the application of a 0.4-T SMF significantly increased ( p < 0.05) the viability of the NK92-MI cells. Furthermore, the inhibitor tests indicated that the SMF affected cell viability by activating multiple MAPK signaling pathways (ERKs, JNKs, and p38-MAPK). Finally, SMF pre-exposure for 48 hr significantly improved the killing activity of the NK92-MI cells ( p < 0.05). That is, pre-exposure to SMF increased the viability of the NK92-MI cells and improved their killing ability against K562 tumor cells. In general, the present results suggest that NK cells pre-exposed to 0.4-T SMF show potential as a tool for immune-therapy treatment of cancer.